Aggregation‐induced circularly polarized luminescence and delayed fluorescence enabled by activating high‐level reverse intersystem crossing - Ke Wang; Xinwen Ou; Xiaofei Niu; Zhenghao Wang; Fengyan Song; Xiaobin Dong; Wu‐jie Guo; Hui‐Qing Peng; Zujin Zhao; Jacky W. Y. Lam; Jianwei Sun; Hongkai Wu; et al. (Aggregate)
Abstract Circularly polarized luminescence (CPL) materials with delayed fluorescence have attracted much attention due to their ability to efficiently trap triplet state excitons, thereby improving the photoluminescence quantum yields of CPL materials. However, much effort has been normally focused on the utilization of T1 excitons but seldom on the utilization of higher excited triplet state Tn (n > 1) excitons. Rational manipulation of higher excited triplet state Tn (n > 1) excitons and suppression of Kasha's rule of CPL materials remains a major challenge. Herein, two gold complex enantiomers ((R/S)‐BPAuBC) based on axially chiral binaphthyls and 3,6‐Di‐tert‐butylcarbazole groups are synthesized and systematically investigated. These materials exhibit aggregation‐induced circularly polarized delayed fluorescence. Circularly polarized delayed fluorescence was found to be enabled by activating high‐level reverse intersystem crossing (hRISC). The anti‐Kasha phosphorescence at 77 K proves that the exciton has a large population in the high‐lying triplet state T2, which allows the effective hRISC process to cross back to the singlet state S1 and emit delayed fluorescence. In addition, CPL “on–off” switching is further achieved in nanoparticles by acid–base stimulus, showing its potential as an acid–base responsive material.